2019
DOI: 10.1073/pnas.1819016116
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae filamentation promotes chitin surface attachment at the expense of competition in biofilms

Abstract: Collective behavior in spatially structured groups, or biofilms, is the norm among microbes in their natural environments. Though biofilm formation has been studied for decades, tracing the mechanistic and ecological links between individual cell morphologies and the emergent features of cell groups is still in its infancy. Here we use single-cell–resolution confocal microscopy to explore biofilms of the human pathogenVibrio choleraein conditions mimicking its marine habitat. Prior reports have noted the occur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 64 publications
(100 reference statements)
2
53
0
Order By: Relevance
“…To test for biofilm growth on chitin, we used a customized microfluidic assay in which pieces of chitin (sterilized shrimp shell) were immobilized, colonized with V. cholerae inoculum, and perfused with a defined seawater medium (61, 62). Attachment and subsequent biofilm growth on the chitin can then be quantified using confocal microscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test for biofilm growth on chitin, we used a customized microfluidic assay in which pieces of chitin (sterilized shrimp shell) were immobilized, colonized with V. cholerae inoculum, and perfused with a defined seawater medium (61, 62). Attachment and subsequent biofilm growth on the chitin can then be quantified using confocal microscopy (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, filamentous E. coli cells were observed to deform upon hydrodynamic forces as investigated in a microfluidic device, regardless of whether they were growing or non-growing cells due to their plasticity [42]. In turn, it was shown that cells of Vibrio cholerae filamenting strain gained a competitive advantage in colonizing and spreading on particles of chitin, the material Vibrio species depend on for growth [43]. Filamentation allowed the creation of a mesh network of cells through physical entanglement and independent of cell-cell adhesion components and the major polysaccharide for the V. cholerae biofilm matrix.…”
Section: Discussionmentioning
confidence: 99%
“…To address the issue of which forces promote and maintain diversity in biofilms, Katrina Harris (laboratory of Vaughn Cooper, University of Pittsburgh, Pittsburgh, PA) described an evolution study in which biofilm-grown P. aeruginosa became highly diverse within 600 generations, with the diversity driven at least partially by the high frequency of appearance of mutator strains (8). Carey Nadell (Dartmouth College, Hanover, NH) described the ability of some V. cholerae strains to form filamentous cells that were capable of wrapping around and colonizing chitin fragments more efficiently than nonfilamentous V. cholerae (9). This ability was independent of known biofilm factors such as the vps polysaccharide locus and may confer an advantage in the environment, permitting V. cholerae to colonize chitinous surfaces such as crustaceans.…”
mentioning
confidence: 99%